NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI SUROAN: Studi di Desa IV Suku Menanti, Sindang Dataran Kabupaten Rejang Lebong - Krismoniansyah, Roby; Warsah, Idi; Putra jaya, Guntur; Abdu, Muhammad (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2020)
Merging between Islamic religion and Javanese cultural behavior has become an interesting phenomenon for any study related to religion. This is supported by the strong Javanese people’s belief in their tradition and therefore cannot be abandoned. Some people may assume that such a tradition is against religious teachings, especially Islam. Apart from that, this study sought to see another side of the tradition, especially the Suroan’s tradition in the Javanese community in Sindanti Dataran Menanti village, Rejang Lebong regency, Bengkulu, whether there were values ​​in Islamic education. To answer this problem, a qualitative approach was used by conducting direct observations and in-depth interviews. This study concluded that there were some Islamic education values ​​such as (I'tiqodiyah) which represented the value ​​related to faith such as the faith in Allah SWT; Educational value (Amaliyah) that was associated with behavior such as worshiping education; and educational value (Khuluqiyah) which was related to ethics (morals) aiming to avoid oneself from negative behavior and decorate oneself with commendable behavior.